Peningkatan Hasil Belajar Siswa Pada Materi PAI Dengan Model Problem Based Learning di SMKN 1 Tarusan - Nova Yanti (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This study aims to improve the learning outcomes of 10th-grade students at SMKN 1 Koto XI Tarusan in Islamic Religious Education using the Problem-Based Learning (PBL) method. This Classroom Action Research was conducted in two cycles, each comprising planning, implementation, observation, and reflection stages. The results revealed an improvement in students' learning outcomes, with learning mastery increasing from 35.7% in the pre-cycle to 60% in the first cycle and reaching 85% in the second cycle. The PBL method encouraged active student engagement through group discussions and solving real-world problems. This success was influenced by the teacher's role as a facilitator, enhanced student participation, and the use of relevant learning media. Thus, the PBL method effectively improved students' learning outcomes while fostering critical thinking, collaboration, and problem-solving skills.